PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN WISATA AIR TERJUN BATANGKOBAN DI DESA LUBUK AMBACANG KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Manullang, Kristian H; Yoza, Defri; Oktorini, Yossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Batangkoban Waterfall located in Lubuk Ambacang Village. This waterfall has uniqueness, which is the form of the waterfall with characteristic of seven levels that have different heights. The purpose of this research is to determine the condition and the potential of tourism object and to know the form of local community participation in the providing facilities and infrastructure of the attractions Batangkoban Waterfall. This research uses observation method, questionnaire and literature study. The result of this research shows that Batangkoban Waterfall becomes the source of fresh water supply. The people around the waterfall also participate in managing the natural waterfalls, namely as a tour guide, transportation service providers for visitors in the form of speed boat, vehicle parking providers, parking attendants, food and beverage sellers and as a supporter of nature conservation and waterfall attractions by taking care the facilities and infrastructure previously provided by the local government. Keywords: Batangkoban Waterfall, Participation, Community.